Insomnia and Anxiety - Carney, Colleen E.; Edinger, Jack D.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The statistics show that as much as twenty percent of the population suffers from chronic insomnia$1 (Band one-fourth of those with the condition eventually develop an anxiety disorder. As comorbid conditions, they contribute to any number of physical and social problems. Yet too often insomnia is undiagnosed, or treated as merely a symptom of the patient$1 (Bs anxiety. Insomnia and Anxiety is the first clinician guidebook that considers the evaluation and management of insomnia and related sleep disturbances that occur conjointly with the common anxiety disorders. By exploring the ways that one condition may exacerbate the other, its authors present robust evidence of the limitations of viewing insomnia as secondary to GAD, agoraphobia, PTSD, and others in the anxiety spectrum. The book reviews cognitive and emotional factors common to anxiety and sleep disorders, and models a cognitive-behavioral approach to therapy in which improved sleep is a foundation for improved symptom management. Beginning and veteran practitioners alike will find vital insights into all areas of these challenging cases, including: Diagnostic and assessment guidelines. Cognitive-behavior therapy for insomnia. Behavioral strategies for managing insomnia in the context of anxiety. Cognitive strategies for managing comorbid anxiety and insomnia. Sleep-related cognitive processes. Pharmacological treatment considerations. Insomnia and Anxiety is highly useful to clinical psychologists given the range of treatment strategies it describes and to researchers because of its emphasis on the theoretical and empirical bases for its interventions. In addition, its accessible style makes it an excellent training tool for students of therapy and psychopathology.s
Anxiety and Insomnia: An Overview -- Considerations for Assessment -- Anxiety Disorders and Accompanying Insomnia -- Cognitive Behavior Therapy for Insomnia: Treatment Considerations -- Medication Considerations -- Behavioral Strategies for Managing Insomnia -- Sleep-Related Cognitive Processes -- Cognitive Strategies for Managing Anxiety and Insomnia -- Other Issues in Managing the Sleep of Those with Anxiety.
Keywords: Philosophy (General).; Psychotherapy; Psychology, clinical; Psychology; Clinical Psychology; Psychotherapy